Development of plasticized edible films from Opuntia ficus-indica mucilage: A comparative study of various polyol plasticizers. (15th June 2018) - Gheribi, Rim; Puchot, Laura; Verge, Pierre; Jaoued-Grayaa, Najeh; Mezni, Mohamed; Habibi, Youssef; Khwaldia, Khaoula
Graphical abstract: Highlights: Cactus mucilage was used as a sustainable biomaterial to develop edible films. The plasticizing effect of four polyols on mucilage films was investigated. PEG 400-plasticized films showed higher thermal stability than the other films. The highest water vapor barrier properties were obtained with sorbitol. The highest elongation at break was provided by films plasticized with glycerol. Abstract: Mucilage polysaccharide was extracted from Opuntia ficus-indica cladodes ( Cactaceae ) and its composition was determined by sugar analysis using HPLC-RID and its structural features were elucidated by FTIR and 1 H and 13 C NMR. Films from the extracted mucilage were loaded at 40% (w/w) with glycerol, sorbitol, PEG 200 or PEG 400. The physical, thermal, mechanical and barrier properties of the obtained films were investigated. The highest water vapor barrier properties of plasticized mucilage films were obtained with sorbitol reaching water vapor permeability (WVP) values up to 3 times lower than the other films. The tensile strength (TS) values of films plasticized with PEG 200 and sorbitol were about 2 times higher than those of glycerol-plasticized films. The significant effect of polyol type plasticizers on the different properties of mucilage edible films was related to their structural features that promote different interactions with mucilage polysaccharides as demonstrated by FTIR and thermal properties.